Pulse crops research in India - ASTHANA, A N (The Indian Journal of Agricultural Sciences, 2013)
India grows such a variety of pulse crops which none of the countries in the world grows. Though the area under pulses has been fluctuating between 22 and 24 million ha, an improvement in production and productivity was 12.42 million tonnes and 520 kg/haduring 1964-65 to 14.12 million tonnes and 609 kg/ha during 1994-95 during to development of new varieties and technologies. Special features, and areas of adoption of varieties of different pulse crops in different regions of the country are given consisely. Total germplasm collection, evaluation and conservation under All-India Coordinated Pulses Improvement Project are also highlighted. Future thrust areas are also suggested in respect of genetic enhancement of yield and grain quality, cropping systems research, integrated nutrient and drought, water and pest management.